2021
DOI: 10.1177/2192568221998306
|View full text |Cite|
|
Sign up to set email alerts
|

Perioperative Complications of Surgery for Degenerative Cervical Myelopathy: A Comparison Between 3 Procedures

Abstract: Study Design: Retrospective comparative study. Objectives: To compare the perioperative complications of propensity score-matched cohorts of patients with degenerative cervical myelopathy (DCM), who were treated with anterior cervical discectomy and fusion (ACDF), posterior laminectomy with fusion, or laminoplasty. Methods: The Humana PearlDiver Patient Record Database was queried using the International Classification of Diseases (ICD-9 and ICD-10) and the Current Procedural Terminology (CPT) codes. Propensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…The ACDF was reported to reduce intraoperative bleeding and better preserve cervical lordosis, while laminoplasty retained more ROM ( Montano et al, 2019 ). Recently, Mohamed et al reported a higher incidence of dysphagia, new-onset cervicalgia, and increased incidence of recurrence in patients with ACDF compared to those with laminoplasty ( Mesregah et al, 2021 ). In a prospective cohort study of 60 patients with lordotic cervical spine, Liang et al reported similar sagittal alignment results between ACDF and laminoplasty, while ACDF was associated with poor cervical lordosis preservation ( Liang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ACDF was reported to reduce intraoperative bleeding and better preserve cervical lordosis, while laminoplasty retained more ROM ( Montano et al, 2019 ). Recently, Mohamed et al reported a higher incidence of dysphagia, new-onset cervicalgia, and increased incidence of recurrence in patients with ACDF compared to those with laminoplasty ( Mesregah et al, 2021 ). In a prospective cohort study of 60 patients with lordotic cervical spine, Liang et al reported similar sagittal alignment results between ACDF and laminoplasty, while ACDF was associated with poor cervical lordosis preservation ( Liang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…They found that disk heights postoperatively were significantly larger than preoperative disk heights. Excessive distraction or overstuffing of the disk space during ACDF may lead to increased strain on the posterior ligaments and facet joints, thereby leading to posterior neck pain 38,42. Mesregah et al 43 found similar results in their study—they found significantly lower rates of new-onset cervicalgia after laminoplasty compared with ACDF and laminectomy with fusion.…”
Section: Discussionmentioning
confidence: 79%
“…Laminoplasty originated in the 1970s as an alternative to laminectomy 1 . Since its adoption, literature has been published establishing that laminoplasties offer equally robust clinical outcomes as other surgical techniques, including laminectomy and fusion and anterior cervical discectomy and fusion (ACDF), in treating cervical myelopathy (CM) [2][3][4][5][6][7][8] . Laminoplasty also offers several unique advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Veeravagu et al analyzed 35,962 patients with CM from 2006 to 2010 and reported that 865(2.4%) underwent laminoplasty, a finding similar to that of our study21 . Mesregah et al analyzed 15,524 patients with degenerative CM, of whom 3.3% had laminoplasty8 . Three prior studies analyzed over 50,000 patients with CM from the Nationwide Inpatient Sample (NIS) from 2001 to 2010 and concluded that ACDFs comprised 63.3% of cases12,22,23 .…”
mentioning
confidence: 99%